KAJIAN KETAHANAN BETON DENGAN TAMBAHAN CAMPURAN FLY ASH DAN LIMBAH KARBIT DALAM MEDIA ASAM DAN GARAM (DURABILITY STUDY OF SELF COMPACTING CONCRETE WITH ADDED A MIXTURE OF FLY ASH AND CALCIUM CARBIDE WASTE IN ACID AND SALT MEDIUM) - Illen Stevani; Titin Anita Zaharah; Imelda Hotmarisi Silalahi (Tanjungpura University, 2023)
Cement is one of the building blocks of concrete. However, it releases about one ton of carbon dioxide (CO2) gas for every ton of cement produced. Therefore, it is necessary to replace cement in the manufacture of concrete. It is known that a mixture of fly ash and calcium carbide waste has a chemical composition that resembles cement containing silica, alumina, and calcium oxide compounds so that it has the potential to replace cement in making self-compacting concrete. This research was conducted by utilising fly ash waste and carbide waste as additional materials to replace the use of cement by 35% in self compacting concrete. The composition of the waste used in the concrete mix in this study consisted of 25% fly ash waste and 10% calcium carbide waste. Analysis of the elemental composition of self-compacting concrete containing fly ash and calcium carbide waste was obtained from XRF data, the compressive strength of self-compacting concrete samples was tested, their resistance in acid and salt media was studied through the results of compressive strength test analysis, then compared with self-compacting concrete containing 100% cement. The XRF results showed that the elemental composition of the mixture of fly ash, calcium carbide waste, and cement was similar to that of cement alone, but the CaO and SiO2 content of the mixture was still higher than that of cement alone. Based on the compressive strength test analysis results, it was found that the compressive strength values of the self-compacting concrete samples were lower than the compressive strength values of the control of self-compacting concrete samples (cement only). Self-compacting concrete samples soaked in acid and salt media for 28 days showed a decrease in compressive strength, both in self compacting concrete containing a mixture of fly ash, calcium carbide waste, and cement, and concrete containing only cement. The compressive strength values of the fly ash and calcium carbide waste on self-compacting concrete samples in this study were at the range of 28 MPa to 29 MPa, still within the SNI 2847-2019 quality standard, which is the normal concrete quality standard with a compressive force of 15-30 MPa, even though they have been exposed to acid or salt. This allows efforts in replacing cement in self compacting concrete by adding the composition of fly ash waste and calcium carbide waste.